Operational independence for the NHS. (22nd July 2008) - Vaithianathan, Rhema; Lewis, Geraint
Abstract : Ara Darzi didn't suggest freedom from government control in his review of the English NHS, but it might sound attractive to many health workers. Rhema Vaithianathan and Geraint Lewis show how it could work using the theoretical framework of independent central banks